Optimizing the value of bioinks and robotics to advance in vivo bioprinting: review - Dehli, Friederike; O'Dwyer Lancaster-Jones, Oscar; Duarte Campos, Daniela Filipa (Current opinion in biotechnology, 2025)
In vivo bioprinting strategies aim at facilitating immediate integration of engineered tissues with the host’s biological system. As integral parts of current bioprinting technologies, bioinks and robotics should be holistically considered for new biomedical applications. This implies that chosen bioinks should exhibit rheological properties that are compatible with the fabrication method and vice versa, bioprinting tools might need to be redesigned and reconstructed to fit the characteristics of the needed bioinks that after solidification act as supporting matrices for living cells. In this piece, we identify current challenges in merging the best of these two principles, we highlight relevant studies that have addressed this need, and we propose ideas how to approach this challenge in the next years.
Gesehen am 10.07.2025